Case report: Peptide receptor radioligand therapy in metastatic pediatric neuroendocrine tumors - Hlongwa, Khanyisile; Kolade, Olumayowa; Alnabulsi, Abdulilah; Steyn, Rachelle; Brink, Anita; Prasad, Vikas; More, Stuart (Frontiers in Nuclear Medicine, 2023)
Neuroendocrine tumours (NETs) are not commonly diagnosed in children. Metastatic NETs tend to have poor outcomes and this is seen in adult and paediatric populations. The role of Somatostatin Receptor (SSTR) Imaging using [ 68 Ga]Ga-DOTA-TATE for imaging and Peptide receptor Radionuclide Therapy (PRRT) with [ 177 Lu]Lu-DOTA-TATE in children is currently not well established. The guidelines for treating paediatric neuroendocrine tumours is still lacking. Extensive trials have been done in adult patients which demonstrated improved survival in metastatic NET with PRRT using [ 177 Lu]Lu-DOTA-TATE. We present two paediatric patients with metastatic NETs who have been imaged with [ 68 Ga]Ga-DOTA-TATE PET/CT and treated with [ 177 Lu]Lu-DOTA-TATE therapy.